Fairness in antitrust : protecting the strong from the weak - Ayal, Adi (Oxford : Hart Publishing, 2014)
This text assesses how modern policy has hijacked popular support - based on traditional conceptions of political and economic power - to combat market power in narrowly defined micro-markets.
Includes bibliographical references and index.
Keywords: Antitrust law